COMPARATION OF MASTOID TRIANGLE AREA MEASUREMENT TECHNIQUES USING VOLUME RENDERING POST PROCESSING AND MULTI PLANAR REFORMATION - Maduma, Anggi Tiur; Sensusiati, Anggraini Dwi; Sari, Amillia Kartika (Faculty of Vocational Studies, Universitas Airlangga, 2020)
Background: Identification in the anthropology of the forensic world using radiographic methods can be evaluated from variations in the human skeleton. The skull is the most dimorphic part of the skeleton, precisely in the temporal bone, namely the mastoid process. The use of advanced radiological technology in the evaluation of the mastoid process in humans can be done using the CT scan modality. Purpose: To determine the measurement results of the total area of the mastoid triangle using post processing volume rendering and multi planar reformation. Method: This type of research is an analytic observational study with a retrospective approach. The number of samples used were 152 raw data of patients with criteria aged 26-65 years and without any pathological changes in the mastoid process area. This research uses simple random sampling technique. Measurements were carried out 10 times by using 2 gauges, and using 3D slicer software on volume rendering and multi planar reformation reconstruction data. Data were analyzed using the free sample T test. Result: Measurer A produces total area of mastoid triangle using volume rendering is 1165.72 ± 1.2506 and multi planar reformation is 1145.84 ± 1.46512, with a significance value of 0.204 (p > 0.05). Similar results were obtained by measuring B. Measurer A produced a total area of mastoid triangle using volume rendering is 1159.91 ± 1.29691 and an multi planar reformation is 1146.56 ± 1.4606, with a significance value of 0.400 (p > 0.05). Conclusion: The results indicated that there was no significant difference in the results of measuring the total area of mastoid triangle using post processing volume rendering and multi planar reformation.